The Use of Vitamin K2 in Patients With Parkinson's Disease and Mitochondrial Dysfunction (PD-K2): A Theranostic Pilot Study in a Placebo-Controlled Parallel Group Design - Prasuhn, Jannik; Kasten, Meike; Vos, Melissa; König, Inke R.; Schmid, Sebastian M.; Wilms, Britta; Klein, Christine; Brüggemann, Norbert (Frontiers in Neurology, 2021)
Background. Despite rapid advances in research on Parkinson’s disease (PD), in particular in the elucidation of genetic contributions, no disease-modifying therapy has become available to date. Objectives. In the proposed project, we aim to investigate the potential effects of vitamin K2 (long-chain menaquinone 7, MK-7) in genetically determined PD with mitochondrial dysfunction. Methods. A total of 130 study participants (26 biallelic Parkin/PINK1 mutation carriers, 52 sporadic PD patients, and 52 healthy controls) will receive the trial medication (MK-7 or placebo for one week). 31P-Magnetic resonance spectroscopy imaging (31P-MRSI, primary endpoint) as well as other advanced neuroimaging methods, clinical assessment, including quantitative movement analysis, and biomarker sampling will be applied pre- and post-intervention. Innovation. The proposed project is highly translational as it builds on compelling mechanistic data from animal studies as well as on a small preliminary data set in humans. Patients are selected based on their mutation-related mitochondrial dysfunction and compared to disease and a healthy control group in a personalized medicine approach. We will further investigate how neuroimaging and blood-derived biomarkers can predict individual treatment response in sporadic PD. Clinical Trial Registration. This study was registered at the German Clinical Trial Registry (DRKS, DRKS00019932) on the 19th of December 2019.